Decentralized Artificial Intelligence on Blockchain - Buch, Yatrik; Hasan, Mosin; Swadas, Prashant (International Journal of Computer Sciences and Engineering, 2019)
Blockchain’s integration with various domains beyond cryptocurrency has produced exciting results and innovative products. Blockchain’s capabilities of being distributed peer-to-peer network, scalability, reliability and security has potential to solve many challenges faced by AI and at the same time add exciting features to it. This article analyses and reviews many existing research where Blockchain is integrated with AI. These research works have produced many encouraging results for data privacy, security, distributed processing and trustless collaboration. Blockchain has also contributed to enhance security of the AI system and bring trust among various AI systems. Cryptocurrency has also added trading capabilities to AI and encouraged models like AI as Service. This article also discusses scope for future research work. With more maturity and feature fullness, Blockchain is poised to become one of the most suitable platforms for decentralized AI applications.